Development of E-Comic Media on the Addition Operation of Iteger Numbers Phase B Applied in Science Learning - Novia Susanti; Ramalis Hakim; Darmansyah; Fetri Yeni (Jurnal Penelitian Pendidikan IPA, 2025)
Learning media is one of the supports in growing and increasing students' interest in learning. However, based on the results of initial research through interviews conducted at SDN 14 Labuah, Tanjung Raya District, Agam Regency, it was found that the school did not have adequate learning media and did not utilize them well. Teachers only used existing textbooks and used the whiteboard as a medium for delivering lesson materials. This study aims to develop interactive e-comic learning media for mathematics subjects on the material of integer addition operatioans for third-grade elementary school students. The background of this study is the low interest and learning outcomes of students (only 40% achieved the KKM) at SDN 14 Labuah due to inadequate learning media. This study uses the 4D model Research and Development (R&D) method, which includes the Define, Design, Development, and Disseminate stages. However, this study focuses on the Development stage, namely validation and practicality tests. Data collection was carried out through observation, interviews, and questionnaires. The results showed that the e-comic media was declared highly feasible with validation scores of 85.71% from media experts, 88.64% from material experts, and 91.66% from language experts. Furthermore, this media was also deemed highly practical based on teacher (93.18%) and student (93.75%) responses. Thus, it was concluded that this e-comic media is feasible to use and highly effective as a mathematics learning medium in grade III of elementary school.